Geophysical, Geochemical and Structural Features of Chromite Ore in Kuradawe Village/ Mawat Ophiolite Complex, Kurdistan Region, NE Iraq - Mirza, Tola A.; Ameen, Taher H.; Al-Hakari, Salim H. Sulaiman (Sulaimani Journal for Pure and Applied Sciences, 2016)
Small lensoidal bodies of massive and disseminated chromitites have been examined in association with ultramafic rocks of the Mawat Ophiolite Complex (MOC), Iraqi Zagros Thrust Zone, Northeastern Iraq. The Chromites ore have variable thickness enveloped by dunite and of, exhibiting transitional boundaries to harzburgitic host rocks. The primary Chromite composition exhibits high Cr varieties; the average Cr# of Chromite is 0.714, with < 0.3 % TiO2 content, which may reflect the crystallization of Chromite from boninitic magma. The result of the gravity survey leads to lateral delineation of the ore body and estimates an area of about 2800 m2. The thicknesses of different Chromite pods were estimated to be in the range of 10 – 35 m. Structural feature show that such ore bodies have internal structure making angle of 10–12 degrees with dunite wall and surrounding peridotite which indicates that Chromite ore subconcordant type.
Keywords: Geophysical,Gravimeter,Bouguer gravity